Knowledge, attitudes and practices on malaria transmission in Mamfene, KwaZulu-Natal Province, South Africa 2015 - Pinky N. Manana; Lazarus Kuonza; Alfred Musekiwa; Hluphi D. Mpangane; Lizette L. Koekemoer (BMC, 2017)
Abstract Background In South Africa malaria is endemic in Mpumalanga, Limpopo and the north-eastern areas of KwaZulu-Natal provinces. South Africa has set targets to eliminate malaria by 2018 and research into complementary vector control tools such as the Sterile Insect Technique (SIT) is ongoing. It is important to understand community perceptions regarding malaria transmission and control interventions to enable development of community awareness campaign messages appropriate to the needs of the community. We aimed to assess knowledge, attitudes, and practices regarding malaria transmission to inform a public awareness campaign for SIT in Jozini Local Municipality, Mamfene in KwaZulu-Natal province. Methods We conducted a cross-sectional survey in three communities in Mamfene, KwaZulu-Natal during 2015. A structured field piloted questionnaire was administered to 400 randomly selected heads of households. Descriptive statistics were used to summarize data. Results Of the 400 participants interviewed, 99% had heard about malaria and correctly associated it with mosquito bites. The sources of malaria information were the local health facility (53%), radio (16%) and community meetings (7%). Approximately 63% of the participants were able to identify three or four symptoms of malaria. The majority (76%) were confident that indoor residual spraying (IRS) kills mosquitoes and prevents infection. Bed nets were used by 2% of the participants. SIT knowledge was poor (9%), however 63% of the participants were supportive of mosquito releases for research purposes. The remaining 37% raised concerns and fears, including fear of the unknown and lack of information on the SIT. Conclusion Appropriate knowledge, positive attitude and acceptable treatment-seeking behaviour for malaria were demonstrated by members of the community. Community involvement will be crucial in achieving success of the SIT and future studies should further investigate concerns raised by the community. The existing communication channels used by the malaria control program can be used; however additional channels should be investigated.